The Effect of Problem-Based Learning Integrated Local Wisdom on Student Hots and Scientific Attitude - Hikmawati Hikmawati; I Wayan Suastra; Ketut Suma; A.A. Istri Agung Rai Sudiatmika; Rohani Rohani (Postgraduate, University of Mataram, 2021)
The purpose of the study was to analyze the effect of Problem-Based Learning (PBL) integrated with local wisdom on Higher-Order Thinking Skills (HOTS) and students' scientific attitudes. Local wisdom used is a tourist objects on the island of Lombok. The topic of learning is the interaction of living things on Senggigi Beach, Sesaot Forest, and Mount Rinjani. The research method used is quantitative with a posttest only control group design. The population of this study includes 6 classes with 172 7th grade students at SMP Negeri 16 Mataram. Samples were taken using cluster random sampling technique, class 7C became the experimental class (32 students), while class 7F became the control class (21 students). The HOTS test instrument is in the form of an essay while the student's scientific attitude instrument is in the form of an observation sheet. Statistical analysis used one-way MANOVA and analyzed using SPSS 25 application. Hypothesis test results showed differences in HOTS and students' scientific attitudes with PBL models and conventional learning. The mean of HOTS and scientific attitude in the experimental class is superior to the control class. The test of between-subjects effects for the HOTS variable and scientific attitude shows differences in HOTS and scientific attitudes due to differences in learning models. Therefore, the PBL model integrated with local wisdom has an effect on HOTS and students' scientific attitudes.